Hydrogen influence on generalized stacking fault energies of Zr 0001 basal plane: a first-principles study. Issue 59 (6th June 2016) - Hou, Songjun; Lei, Huaping; Zeng, Zhi
Abstract : The influence of hydrogen on the Generalized Stacking Fault (GSF) energies of the 0001 basal plane along the 〈101̄0〉 and 〈112̄0〉 directions in HCP Zr has been investigated by using the first-principles calculations and the chemical bonding analysis. Abstract : The influence of hydrogen on the Generalized Stacking Fault (GSF) energies of the 0001 basal plane along the 〈101̄0〉 and 〈112̄0〉 directions in HCP Zr has been investigated by using the first-principles calculations. The variations of GSF energies are studied with respect to different distances of H atoms away from the glide plane and different hydrogen concentrations around the glide plane. The results have shown that the ⅓〈101̄0〉0001 GSF energy is drastically reduced when H atoms are located nearby the glide plane, but H atoms only moderately decrease the ⅓〈112̄0〉0001 GSF energy in proportion. With the increase of H concentration around the glide plane, the GSF energies further greatly reduce with respect to both shift directions. The physical origins of the reduction of GSF energies caused by H atoms have been interpreted based on Bader charge analysis and the structural deformation around the glide plane. The Coulomb repulsion of the positively charged Zr atoms on both sides of the glide plane results in a remarkable decrease of the ⅓〈101̄0〉0001 GSF energy, while the relatively large structural deformation takes precedence over the Coulomb repulsion to determine the ⅓〈112̄0〉0001 GSF energy in the presence of H atoms. Our work proposes a new insight to understand the role of H in the degradation of Zr mechanical performance as cladding materials of nuclear reactors.